2019
DOI: 10.3389/feart.2019.00234
|View full text |Cite
|
Sign up to set email alerts
|

Left High and Dry: Deglaciation of Dogger Bank, North Sea, Recorded in Proglacial Lake Evolution

Abstract: Reconstructions of palaeo-ice sheet retreat in response to climate warming using offshore archives can provide vital analogs for future ice-sheet behavior. At the Last Glacial Maximum, Dogger Bank, in the southern North Sea, was covered by the Eurasian Ice Sheet. However, the maximum extent and behavior of the ice sheet in the North Sea basin is poorly constrained. We reveal ice-marginal dynamics and maximum ice extent at Dogger Bank through sedimentological and stratigraphic investigation of glacial and progl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 134 publications
2
33
0
Order By: Relevance
“…The channel network was buried during subsequent marine transgression which began at around 10 ka at Dogger Bank, with complete inundation occurring around 8.5-8 ka (Brooks et al, 2011;Emery et al, 2019b;Shennan et al, 2000;Sturt et al, 2013). Shallow marine sand, varying in thickness from 0 m up to 25 m, was then deposited during the Late Holocene (Cotterill et al, 2017b;Emery et al, 2019b).The stratigraphy provides an archive of the transition (Cotterill et al, 2017b;Emery et al, 2019a, b), with the incised channels and Horizon Z observed in this study. from MIS 5 marine sediments, through to glacial and terrestrial environments, followed by a return to marine conditions during MIS 1, 11.7 ka to present (Cotterill et al, 2017a, b;Emery et al, 2019a, b;Phillips et al, 2018).…”
Section: Settingmentioning
confidence: 50%
See 4 more Smart Citations
“…The channel network was buried during subsequent marine transgression which began at around 10 ka at Dogger Bank, with complete inundation occurring around 8.5-8 ka (Brooks et al, 2011;Emery et al, 2019b;Shennan et al, 2000;Sturt et al, 2013). Shallow marine sand, varying in thickness from 0 m up to 25 m, was then deposited during the Late Holocene (Cotterill et al, 2017b;Emery et al, 2019b).The stratigraphy provides an archive of the transition (Cotterill et al, 2017b;Emery et al, 2019a, b), with the incised channels and Horizon Z observed in this study. from MIS 5 marine sediments, through to glacial and terrestrial environments, followed by a return to marine conditions during MIS 1, 11.7 ka to present (Cotterill et al, 2017a, b;Emery et al, 2019a, b;Phillips et al, 2018).…”
Section: Settingmentioning
confidence: 50%
“…These channels form part of the extensive networks of post-Last Glacial Maximum North Sea channel fills mapped by the North Sea Palaeolandscape Project (Fitch et al, 2005;Gaffney et al, 2007Gaffney et al, , 2009 and other studies (Cameron et al, 1987;Coughlan et al, 2018;Hepp et al, 2017Hepp et al, , 2019van Heteren et al, 2014;Hijma et al, 2012;Prins and Andresen, 2019;Salomonsen, 1993). The channel network was buried during subsequent marine transgression which began at around 10 ka at Dogger Bank, with complete inundation occurring around 8.5-8 ka (Brooks et al, 2011;Emery et al, 2019b;Shennan et al, 2000;Sturt et al, 2013). Shallow marine sand, varying in thickness from 0 m up to 25 m, was then deposited during the Late Holocene (Cotterill et al, 2017b;Emery et al, 2019b).The stratigraphy provides an archive of the transition (Cotterill et al, 2017b;Emery et al, 2019a, b), with the incised channels and Horizon Z observed in this study.…”
Section: Settingmentioning
confidence: 94%
See 3 more Smart Citations